Hydrogel synthesis by aqueous Diels‐Alder reaction between furan modified methacrylate and polyetheramine‐based bismaleimides. Issue 5 (22nd December 2014) - García‐Astrain, Clara; Algar, Itxaso; Gandini, Alessandro; Eceiza, Arantxa; Corcuera, María Ángeles; Gabilondo, Nagore
ABSTRACT A simple method for preparing cross‐linked hydrogels in an aqueous medium is investigated using Diels‐Alder (DA) "click" reaction, without employing a catalyst. A polymeric diene is first synthesized by the functionalization of poly(2‐aminoethyl methacrylate) hydrochloride with furfural. Suited bisdienophiles are prepared by modification of Jeffamine® ED of different molecular weights with maleic anhydride. Both precursors of the DA coupling are thoroughly characterized before their reactions. The ensuing hydrogels are analyzed in terms of their microstructure, swelling, and rheological behavior, as a function of the reaction conditions. The influence of the molecular weight of the cross‐linker and the furan‐to‐maleimide ratio on the final properties of the hydrogels were also investigated. © 2014 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2015, 53, 699–708